Instagram Sebagai Sumber Berita Nasional: Studi Pada Akun @Antaratv - Azzahra, Adinda; Santoso, Hudi (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
This study analyzes the use of the Instagram account @antaratv in disseminating national news in Indonesia, especially among the younger generation. Using a qualitative descriptive approach, data were collected through in-depth interviews with the manager of the Instagram account @antaratv. The results of the study indicate that Instagram has become an effective platform for disseminating information. The Instagram account @antaratv has successfully adapted a communication strategy by utilizing features such as Reels and attractive visual content, in accordance with the preferences of digital audiences who tend to like short and easy-to-digest information. This study also highlights the importance of journalistic integrity in presenting news, such as the spread of fake news. By utilizing the Diffusion of Innovation theory, this study shows that Instagram users @antaratv reflect successful adaptation to changes in news consumption patterns in the digital era. These findings are expected to provide insight into the development of more effective and reliable information dissemination strategies on social media.